The auotonomy of the fisherrmen comunities to prepare of the oil is important to be developed, where it would help them to decrease the dependence of oil. Another hand, source of alternative energy available in the coastal area. So, to socialized the energy alternatif for them should use andragogy approach The literature study focuses on what learning theory suitable for adult, and what the kind of altemative energy could be improve for them. The study show that student centered learning is suit - Anna Fatchiya (Buletin Ekonomi Perikanan, 2007)
The auotonomy of the fisherrmen comunities to prepare of the oil is important to be developed, where it would help them to decrease the dependence of oil. Another hand, source of alternative energy available in the coastal area. So, to socialized the energy alternatif for them should use andragogy approach The literature study focuses on what learning theory suitable for adult, and what the kind of altemative energy could be improve for them. The study show that student centered learning is suitable for adult, and the kinds of alternative energy could be improve for fisherrmen communities were: thrifty charcoal stove, Pl TM, biodiesel, dan solar energy.